Quem nasce em campina grande é campinense : futebol e sociabilidade na rainha da borborema (1954-1965) - Marques, Giovanna Lopes (2011)
This study aims to historicize a problem: How Campinense Club, club social of the city of Campina Grande, became a popular club? This guild was founded in 1915 by a group of graduates, which they called "Campinense" a social club dedicated to the enjoyment of the city's elites. To investigate the mechanisms that have led to this popularity, was chosen that includes a period from 1954 to 1965, when it was created a department where the professional football club won a string of six consecutive championships, considered the main achievement of its history sports. Were used as research sources Borborema the Journal, a newspaper founded in 1957 and that during the period in question, was the spokesman of the main political groups in the city, which on many occasions were the sponsors of the clubs the same. This newspaper had a daily sports column and introduced the red-black team to Paraíba. Were used, although the club's meeting minutes taken as official documents, which allowed it to be mounted on a puzzle of the club's events, since the information about the Campinense present rather fragmented. Finally, respondents were fans, athletes and leaders who, through his lines in a way pointed out other possibilities such as a club, believed to be aristocratic, has become a passion among the fans, giving rise to this conception to be one that Campinense broke with the established elites of the city.